TEACHER CERTIFICATION DECISION SUPPORT SYSTEM - Sutriana Sutriana; Khozainuz Zuhri; Fatimah Fahurian; Yodhi Yuniarthe (Journal of Technology and Data Science, 2022)
Technology in education in Indonesia has continued to improve throughout the 21st century. This results in a continuous evaluation of the education system, which in turn provides information on educational gaps. SMK Persada Bandar Lampung is an educational institution that has problems in assessing the feasibility of teacher certification, which does not yet have a system where errors often occur in the assessment process. Evaluating the feasibility of teacher certification, which is subjective will take time to process the results. In the process of assessing the feasibility of teachers, certification errors may occur. SMK Persada Bandar Lampung requires a decision support system that is expected to find a solution in the process of determining the best teacher. The decision system for assessingthe feasibility of teacher certification can facilitate data processing of the results of the teacher certification feasibility assessment at SMK Persada Bandar Lampung.Therefore, the researcher proposes a decision support system software engineering by applying Simple Additive Weighting (SAW). This system can later be used to assess the feasibility of teacher certification at SMK Persada Bandar Lampung to assist schools in evaluating the shortcomings and strengths of teacher performance